The control scheme of vehicle steer by wire system by using PD-PID controller - Mohd Zaidi, Mohd Tumari; M.A.M., Nasir; Muhammad Salihin, Saealal; A.W.A. , Aziz; Shahrizal, Saat; Mohd Helmi, Suid; Mohd Riduwan, Ghazali (Centre for Advanced Research on Energy (CARe), 2017)
The control of Vehicle Steer by- Wire (VSBW) system can cause the practical problem due to elimination of mechanical Link between the steering wheel and front wheel. This paper presents the development of PD-PID controller for steering wheel returnability, directional control and wheel Synchronization of a VSBW system PD controller is used to control the returnability of steering wheel while PID controller is used to control the angle of frot wheel. The Ziegler Nichols method is used for tuning the PID parameters. The implementation environment is developed within Labview software. The experimental results are presented in time domains.. The controller! is capable to improve the perfformance Of the system in terms of" steering wheel returnability. directional control and wheel synchronization.